Seed production technology of jute for non-traditional western plateau region of Odisha - Sarkar, Sitangshu; Majumdar, Bijan; Bera, Amit (Indian Farming, 2020)
Quality Olitorius jute seed production can be taken up by the farmers in western Odisha region owing to congenial climatic condition during July-November and the endeavour of jute seed production is much better and remunerative than the traditional paddy cultivation for western Odisha farmers.